NOVEL VALIDATED REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR DETERMINATION OF GLUCOSAMINE, DIACEREIN, AND METHYL SULFONYL METHANE IN MICRO SAMPLE RAT PLASMA AND ITS APPLICATION TO PHARMACOKINETIC AND DISSOLUTION STUDIES - BHAVANI, PODILI; PRASADA RAO, KAMMELA; MOHAN, SEELAM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of this research is to develop and validate a simple, specific, precise, sensitive, cost-effective, and rapid reversed-phase high-performance liquid chromatography method for simultaneous quantification of glucosamine (GLU), diacerein (DIA) and methyl sulfonyl methane in bulk and pharmaceutical dosage forms, and micro-sample of rat plasma using ultraviolet (UV) detection, to perform the studies of drug dissolution from tablets. Methods: Sprague-Dawley rats were used for pharmacokinetic study after intravenous administration of the drug samples at dose 5 mg/kg. The drug samples were extracted by liquid-liquid extraction technique using acetonitrile, which also acted as a deproteinization agent. The separation of the analyte was carried out on a phenomena C18 column with a mobile phase composed of 0.1 % orthophosphoric acid:acetonitrile (80:20 v/v) delivered at a flow rate of 1.0 ml/min, and separation has been monitored by a UV detector, at detection of the wavelength of 285 nm. Results: This method was proven to be linear over a concentration range of 30–450 μg/ml for GLU, 2–30 μg/ml for DIA, and 10–150 μg/ml for methyl sulfonyl methane with a correlation coefficient of 0.999. The retention time of GLU, DIA, and methyl sulfonyl methane were 2.89, 6.32, and 9.87 min, respectively. Recovery of the drugs was found to be in the range of 98.0–102.0%. Validation results were found to be satisfactory and the method applicable for bulk and formulation analysis. Hence, it was evident that the proposed method was said to be a suitable one for the regular analysis and quality control of pharmaceutical preparations which contain these active drugs either individually or in combination. Conclusion: The validation results were in good agreement with acceptable limits. Relative standard deviation values which are less than 2.0% are indicating the accuracy and precision of this method. The usefulness of the method is that the common chromatographic conditions have been adopted for assay, dissolution, and pharmacokinetic studies. This developed method showed reliable, precise, and accurate results under optimized conditions.